PENGARUH BEBAN KERJA DAN KESEHATAN KESELAMATAN KERJA (K3) TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN DOMPU - Asri Raihan; Amirul Mukminin (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to find out and analyze the effect of workload and occupational health and safety (K3) on employee performance at the Office of the National Land Agency, Dompu Regency. Types of associative research. research instrument using a Likert scale questionnaire. The population used was all employees at the Dompu Regency National Land Agency office as many as 53 people with details of 32 civil servant employees and 21 non-employee government employees (PPNP), the sample in this study were 32 civil servants. The sampling technique used is porposive sampling. Data collection techniques in this study were observation, interviews, questionnaires and literature study. Data analysis techniques using validity test, reliability test, classical assumption test, multiple regression, multiple correlation coefficient, t test and f test. The results of the study show that workload and occupational health and safety (K3) have a simultaneous effect on employee performance at the Office of the National Land Agency, Dompu Regency.